Neuroprotective Effects of Berberine in Alzheimer's Disease: Review Article (Journal of Pharma Insights and Research, 2025)
Alzheimer's disease (AD) is one of the predominant causes of dementia worldwide. It is characterized by progressive neurodegeneration, cognitive decline, and distinctive neuropathological features including β-amyloid plaques and neurofibrillary tangles. Current therapeutic interventions provide only symptomatic relief, emphasizing the need for disease-modifying treatments. Berberine, an isoquinoline alkaloid derived from various medicinal plants, is being recognized as a promising treatment for AD treatment due to its diverse pharmacological properties. Recent studies have shown the berberine's ability to modulate multiple pathological processes in AD, including reduction of amyloid-β production, inhibition of tau hyperphosphorylation, enhancement of cholinergic transmission, and attenuation of oxidative stress and neuroinflammation. The capacity of berberine to cross the blood-brain barrier and its established safety profile further support its potential as a neurotherapeutic agent. Berberine acts by altering AMPK signaling, NF-κB regulation, and modulation of cholinergic systems. It also shows remarkable effects on mitochondrial function, synaptic plasticity, and neuronal survival. Additionally, berberine exhibits synergistic effects when combined with conventional AD treatments, suggesting its potential role in combination therapy.